Two distinct factors bind to the rabbit uteroglobin TATA-box region and are required for efficient transcription. - Klug, J; Knapp, S; Castro, I; Beato, M (1994)
The rabbit uteroglobin gene is expressed in a variety of epithelial cell types like the lung Clara cells and the glandular and luminal epithelial cells of the endometrium. Expression in Clara cells is on a high constitutive level, whereas expression in the rabbit endometrium is under tight hormonal control. One important element of the rabbit uteroglobin gene mediating its efficient transcription in two epithelial cell lines from human endometrium (Ishikawa) and lung (NCI-H441) is its noncanonical TATA box (TACA). Here, we show that two factors (TATA core factor [TCF] and TATA palindrome factor [TPF]) different from the TATA-box binding protein bind to the DNA major groove at two adjacent sites within the uteroglobin TATA-box region and that one of them (TCF) is specifically expressed in cell lines derived from uteroglobin-expressing tissues. The binding sites for TCF and TPF, respectively, are both required for efficient transcription in Ishikawa and NCI-H441 cells. Mutation of the TACA box, which we show is a poor TATA box in functional terms, to a canonical TATA motif does not affect TCF and TPF binding. Therefore, we suggest that the function of the unusual cytosine could be to reduce rabbit uteroglobin expression in cells lacking TCF and that the interaction of TATA-box binding protein with the weak TACA site is facilitated in TCF- and TPF-positive cells.